2007
DOI: 10.1002/jcla.20186
|View full text |Cite
|
Sign up to set email alerts
|

Chagas' disease: IgG isotypes against cytoplasmic (CRA) and flagellar (FRA) recombinant repetitive antigens of Trypanosoma cruzi in chronic Chagasic patients

Abstract: The wide range of clinical Chagas' disease manifestations, of which heart involvement is the most significant, because of its characteristics, frequency and consequences, and lack of treatment and cure, justify research in this area. Specific immunoglobulin G (IgG) antibody subclasses have been associated with human Chagas' disease. Thus, in this study, the profile of IgG subclasses against cytoplasmic (CRA) and flagellar (FRA) recombinant repetitive T. cruzi-specific antigens was correlated with cardiac (CARD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
18
1
Order By: Relevance
“…The evaluation of IgG2 did not reveal a direct association with cardiac involvement, in contrast to other authors, who reported higher reactivity of this IgG2 subclass in patients with different levels of cardiopathy [9][10]12 . On the other hand, high levels of IgG3 were detected, especially in the IND group as compared with the CARD and DIG/ Mix groups.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The evaluation of IgG2 did not reveal a direct association with cardiac involvement, in contrast to other authors, who reported higher reactivity of this IgG2 subclass in patients with different levels of cardiopathy [9][10]12 . On the other hand, high levels of IgG3 were detected, especially in the IND group as compared with the CARD and DIG/ Mix groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, other variables regarding the selected casuistry may be involved, such as the geographical origin of the patients and consequent predominant T. cruzi population, and the length of the infection [7][8][9][10][12][13]26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific production of immunoglobulin G (IgG) against the CRA and FRA antigens has already been demonstrated in chronic chagasic patients by VerÈosa et al [17]. These authors showed that the IgG2 isotype against the FRA antigen was able to distinguish patients with the CARD form from those with the IND form of Chagas disease.…”
Section: Introductionmentioning
confidence: 94%
“…Molecular testing using PCR combined with hybridization have shown promising results and may be used as a confirmatory test (MS 2005). There is, however, a need for other tests to identify CP soon after specific treatment, for a prognosis marker (Verçosa et al 2007, Lorena et al 2008) and for prediction of congenital transmission.…”
Section: What Remains To Be Done With Regard To Follow-up Studies?mentioning
confidence: 99%